A novel machine extraction algorithm for implicit and explicit keywords based on dynamic web metadata of scientific scholars' corpus. (25th May 2023) - Mosbah, Mawloud
Keywords extraction, as an operation to construct metadata, is an important pre-processing task considered by many natural language processing applications such as text summarisation, information retrieval, and clustering of documents. In this paper, we introduce a novel machine extraction algorithm for implicit and explicit keywords. The algorithm relies on a dynamic corpus of similar documents built by information retrieval engines. In addition to the direct utilisation of the keywords for similar documents, our algorithm combines some basic techniques. The given results, compared with some basic methods of the literature, seem to be very promising and we claim also the efficiency of our solution.